Cdc6 as a novel target in cancer: Oncogenic potential, senescence and subcellular localisation. Issue 6 (17th February 2020) - Lim, Nicholas; Townsend, Paul A.
Abstract : Cdc6 is a key replication licencing factor with a pivotal role in regulating the process of DNA replication, rendering it an important investigatory focus in tumourigenesis. Indeed, Cdc6 overexpression has been found to be a feature in certain tumours and has been associated as an early event in malignancies. With a focus on pancreatic cancer, there are evidence of its convergence in downstream pathways implicated in major genetic alterations found in pancreatic cancer, primarily KRAS. There is also data of its direct influence on protumourigenic processes as a transcriptional regulator, repressing the key tumour suppressor loci CDH1 (E‐Cadherin) and influencing epithelial to mesenchymal transition (EMT). Moreover, gene amplification of Cdc6 as well as of E2F (an upstream regulator of Cdc6) have also been found to be a key feature in tumours overexpressing Cdc6, further highlighting this event as a potential driver of tumourigenesis. In this review, we summarise the evidence for the role of Cdc6 overexpression in cancer, specifically that of pancreatic cancer. More importantly, we recapitulate the role of Cdc6 as part of the DNA damage response and on senescence—an important antitumour barrier—in the context of pancreatic cancer. Finally, recent emerging observations suggest that the potential of the subcellular localisation of Cdc6 in inducing senescence. In this regard, we speculate and hypothesise potentially exploitable mechanisms in the context of inducing senescence via a novel pathway involving cytoplasmic retention of Cdc6 and Cyclin E.